Eighth International Symposium "Monitoring of Mediterranean Coastal Areas. Problems and Measurement Techniques" Livorno (Italy) June 2020 - Bonora, Laura; CARBONI, Donatella; DE VINCENZI, MATTEO (Proceedings e report, 2020)
The 8th International Symposium "Monitoring of Mediterranean Coastal Areas. Problems and Measurements Techniques" was organized by CNR-IBE in collaboration with FCS Foundation, and Natural History Museum of the Mediterranean and under the patronage of University of Florence, Accademia dei Geogofili, Tuscany Region and Livorno Province. It is the occasion in which scholars can illustrate and exchange their activities and innovative proposals, with common aims to promote actions to preserve coastal marine environment. Considering Symposium interdisciplinary nature, the Scientific Committee, underlining this holistic view of Nature, decided to celebrate Alexander von Humboldt; a nature scholar that proposed the organic and inorganic nature's aspects as a single system. It represents a sign of continuity considering that in-presence Symposium could not be carried out due to the COVID-19 pandemic restrictions. Subjects are related to coastal topics: morphology; flora and fauna; energy production; management and integrated protection; geography and landscape, cultural heritage and environmental assets, legal and economic aspects.